A Qualitative Study on the Ethical Issues and Islamic Rulings in End of Life Care - Mohd Azaman, Faizatul Najihah; Che Mohamad, Che Anuar; Mahmud, Mek Wok; Abdul Ghani, Muhammad Rasydan; Abdul Rahim, Mohamad Shahrir; Md Tahir, Mohd. Faiz; Shahar, Mohamad Arif; Hashi, Abdurezak Abdulahi; Mohamad, Hasbullah; Ismail, Mohd Nizamuddin; Nanyan, Suhaila; Roslan, Rosazra; et al. (UPM Press, 2021)
The advancement of medical therapy that leads to the discovery of new medical treatments is indeed a blessing to human beings. However, the advancement came with certain ethical concerns involving decisions or procedures which, to a certain extent, contradicting with Islamic values and principles. Amongst the issues that emerged are related to the new diagnosis of brain death, implications of withdrawal and withholding of life support, terminal sedation in palliative care or double effect and the newly advanced medical directives. These issues have raised crucial ethical concern to the Muslim community, particularly to physicians who directly and regularly involved end of life care. Data were gathered through individual interviews: face to face and in-depth semi-structured involving 13 Muslim scholars in Fiqh and Law and Medicine ranging from palliative care, internal medicine, cardiologist, intensivist, family medicine and psychiatrist. Focus group discussions were also conducted twice to further analysed the ethical decision in end of life. Data were subsequently analysed using framework analysis with the aid of the NVivo 11. Our study has identified several other important ethical issues in end of life care, including the recently emerged advance medical directives. However, two fundamental issues currently necessitate serious attention from medical, legal and Islamic perspectives, i.e. (1) the determination of death based on the criteria of brain death and (2) The diagnosis of medical futility. The majority of the experts we interviewed were aware of the issues in end-of-life care. They have responded well and share helpful information, including advance medical directives. Several ethical issues related to the end of life care, including the diagnosis of brain death and medical futility, are important topic to be discussed due to their multifaceted implications, i.e. medical, social, legal as well as Islamic faith